2018
DOI: 10.1017/s1357321718000193
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: reshaping mortality differences within the United Kingdom?

Abstract: Older people are higher contributors to mortality excess and most sensitive to environmental influences, e.g. temperature. As the population ages, variability in temperature is liable to impact a large proportion of life insurance or pension policies in a portfolio. Climate change is projected to significantly affect future mean temperatures. Moreover, future changes in mean temperature are estimated to vary across different regions of the United Kingdom. Accordingly, the present paper investigates the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The association of temperature and mortality was also confirmed in nine European cities [15]. Naqvi and Hall [16] investigated the effect of future mean temperature on older adult mortality in England, Wales, and Scotland and found that there is a U-shape relationship between temperature and mortality and there exist a range of temperatures at which the mortality is higher on its both sides of the range. In Iran, the mortality and diurnal temperature range association study showed that, in high diurnal temperature ranges during the hot season, the Cumulative Relative Risk of non-accidental deaths, and cardiovascular and respiratory deaths increased, whereas in cold season, the high diurnal temperature range caused a lower number of deaths [17].…”
Section: Introductionmentioning
confidence: 82%
“…The association of temperature and mortality was also confirmed in nine European cities [15]. Naqvi and Hall [16] investigated the effect of future mean temperature on older adult mortality in England, Wales, and Scotland and found that there is a U-shape relationship between temperature and mortality and there exist a range of temperatures at which the mortality is higher on its both sides of the range. In Iran, the mortality and diurnal temperature range association study showed that, in high diurnal temperature ranges during the hot season, the Cumulative Relative Risk of non-accidental deaths, and cardiovascular and respiratory deaths increased, whereas in cold season, the high diurnal temperature range caused a lower number of deaths [17].…”
Section: Introductionmentioning
confidence: 82%